High dose and long-term statin therapy accelerate coronary artery calcification. (1st April 2015) - Henein, Michael; Granåsen, Gabriel; Wiklund, Urban; Schmermund, Axel; Guerci, Alan; Erbel, Raimund; Raggi, Paolo
Abstract: Background: In randomized clinical trials statins and placebo treated patients showed the same degree of coronary artery calcium (CAC) progression. We reanalyzed data from two clinical trials to further investigate the time and dose dependent effects of statins on CAC. Additionally, we investigated whether CAC progression was associated with incident cardiovascular events. Methods and results: Data were pooled from two clinical trials: St. Francis Heart Study (SFHS) (419 and 432 patients treated with placebo and 20 mg atorvastatin daily, respectively) and EBEAT Study (164 and 179 patients respectively treated with 10 mg and 80 mg atorvastatin daily). CAC scores were assessed at baseline, 2 years and 4–6 years in SFHS; in EBEAT they were measured at baseline and 12 months. After a short-term follow-up (12 to 24 months) placebo and low dose atorvastatin showed a similar CAC increase, although 80 mg/daily atorvastatin increased CAC an additional 12–14% over placebo (p < 0.001). In the long-term, atorvastatin caused a greater progression of CAC compared to placebo (additional 1.1%, p = 0.04). In SFHS 42 cardiovascular events occurred after the second CT scan. The baseline and progression of CAC were greater in patients with events. However, only baseline CAC and family history of premature cardiovascular disease but not CAC progression were independent predictors of events. Conclusions: Despite a greater CAC increase with high dose and long-term statin therapy, events did not occur more frequently in statin treated patients. This suggests that CAC growth under treatment with statins represents plaque repair rather than continuing plaque expansion.